Spiritualitas Humanis Anti-Korupsi - H. Abdul Hakim; Abdul Sani (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
AbstractThis article examines the role of spiritual integrity and humanistic approaches in combating corruption from theological and philosophical perspectives. Spiritual integrity, understood as an awareness of divine presence in moral oversight—encompassing values such as honesty and responsibility—serves as a fundamental basis for fostering individuals and societies that resist corruption. From a theological standpoint, corrupt practices are considered contrary to spiritual principles that uphold justice. Meanwhile, the philosophical perspective emphasizes self-awareness and ethical reasoning in decision-making, encouraging both individuals and collectives to consider the negative consequences of corrupt actions and the societal resistance against perpetrators. Such resistance plays a crucial role in promoting economic justice and ensuring a better future for societal well-being. Keywords: Spirituality, Theological, Philosophical, Combating Corruption. Abstrak Abstrak Jurnal ini membahas peran integritas spiritual cara-cara humanis dalam memerangi korupsi dari perspektif teologis dan filosofis. Integritas spiritual, dalam makna persentuhan kesertaan Tuhan dalam pengawasan moral akhlak yang mencakup nilai-nilai moral seperti kejujuran dan tanggung jawab, menjadi landasan penting dalam menciptakan individu dan maasyarakat anti korupsi. Dari sudut pandang teologis, tindakan korupsi dianggap bertentangan dengan prinsip-prinsip spiritual yang mengedepankan keadilan. Sementara itu, perspektif filosofis menekankan kesadaran diri dan etika dalam pengambilan keputusan, mendorong individu dan  kolektif untuk mempertimbangkan dampak tindakan negatif dan perlawanan rakyat terhadap mereka yang melakukan tindakan korupsi, yang tentunya sangat luar biasa terhadap kesejahteraan keadilan ekonomi kehidupan bagi masa depan. Kata Kunci: Spiritual, Teologis, Filosofis, Memerangi Korupsi.